Transthoracic parametric Doppler for bedside diagnosis of pulmonary embolism: A pilot study. Issue 4 (23rd December 2019) - Javitt, Marcia C.; Daniels, Lydia; Andraous, Maisa; Chulsky, Semyon; Schatzberger, Rachel; Beck‐Razi, Nira; Guralnik, Ludmilla; Oklander, Boris; Palti, Yoram; Ofran, Yishai; Gaitini, Diana
ABSTRACT: Transthoracic parametric Doppler (TPD), unlike conventional ultrasonography, measures signals originating from movements of pulmonary blood vessel walls. In this pilot study, we tested TPD in 15 patients diagnosed with pulmonary embolism on computed tomography pulmonary angiography. Results were mapped to the upper, middle, and lower thirds of the right lung. In the lower third, TPD yielded 100% specificity and positive predictive value for acute pulmonary embolism. If validated in a larger series, this rapid bedside technique might obviate the need for computed tomography in specific cases. This could be advantageous in patients who are unstable, in intensive care, or have allergies to iodinated contrast material.